Dynamics of Gamma-Band Activity during an Audiospatial Working Memory Task in Humans - Werner Lutzenberger; Barbara Ripper; Laura Busse; Niels Birbaumer; Jochen Kaiser (2002)
The representation of visual objects in short-term memory has been shown to be related to increased gamma-band activity in the electroencephalogram. Using a similar paradigm, we investigated oscillatory magnetoencephalographic activity in human subjects during a delayed matching-to-sample task requiring working memory of auditory spatial information. The memory task involved same-different judgments about the lateralization angle of pairs of filtered noise stimuli (S1 and S2) separated by 800 msec delays of background noise. This was compared with a control condition requiring the detection of a possible change in the background noise volume appearing instead of S2 (volume task). Statistical probability mapping revealed increased spectral activity at 59 Hz over left parietal cortex during the delay phase of the memory condition. In addition, 59 Hz coherence was enhanced between left parietal and right frontal sensors. During the end of the delay and during the presentation of S2, enhanced gamma-band activity at 67 Hz was observed over right frontal and later over midline parietal areas. In contrast, the volume task was characterized by increased left inferior frontotemporal 59 Hz spectral amplitude after S1. Apparently representation of the spatial position of a sound source is associated both with synchronization of networks in parietal areas involved in the auditory dorsal stream and with increased coupling between networks serving representation of audiospatial information and frontal executive systems. The comparison with S2 seemed to activate frontal and parietal neuronal ensembles. Gamma-band activity during the volume task may reflect auditory pattern encoding in auditory ventral stream areas.